PENGARUH INFORMASI AKUNTANSI DAN MAKRO EKONOMI TERHADAP NILAI PERUSAHAAN EFEK SYARIAH - WULANDARI, AYU (Jurnal Akuntansi AKUNESA, 2014)
The purpose of this research is to analyze the influence of accounting and economic macro information on the firm value of Islamic stock in 2009-2013. The population in this study consist of 313 companies listed on the Indonesian Stock Exchange as an Islamic stock in 2013 period and after passing the stage using purposive sampling the sample is only 27 companies with a data sample of accounting information from financial statements, consisting of Debt to Equity Ratio (DER), Current Ratio (CR), Total Assets Turnover (TATO), and Return on Equity (ROE) and Dividend Payout Ratio and non-accounting information in the form of inflation, SBI rates, and the exchange rate effect on firm value of islamic stock. The analysis technique used multiple regression and hypothesis testing using the t-statistic for testing the partial regression coefficients and F-statistics to test the significance of the effect together with the level of significance of 5%. The results showed that simultaneous independen variables affect the firm value of islamic stock. Partially, only the Return On Equity (ROE) and inflation affecting the firm value of islamic stock, while Debt to Equity Ratio, Current Ratio, Total Assets Turnover, Dividend Payout Ratio, SBI interest rate and exchange rate does not affect the value firm value of islamic stock. Key Words:    Debt to Equity (DER), Current Ratio (CR), Total Assets TurnOver (TATO), Return On Equity (ROE), Dividend Payout Ratio, inflation, interest rate, exchange rate, firm value of islamic stock.